2020
DOI: 10.1016/j.artd.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Total Knee Periprosthetic Joint Infection in the Setting of Hematologic Malignancy: Considerations for Management

Abstract: Patients with malignancy are often profoundly immunocompromised due to chemotherapy, placing them at potential increased risk for periprosthetic joint infection (PJI). However, there is little information regarding PJI management in these patients. We describe 4 patients with a history of primary total knee arthroplasty followed by diagnosis of multiple myeloma or Waldenstr€ om macroglobulinemia who received chemotherapy within 4 months prior to PJI. The Musculoskeletal Infection Society major and minor criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Joint aspiration and culture are often used to confirm the diagnosis of PJI, and studies have shown that it is both sensitive and specific in patients at moderate-to-high risk. Direct aspiration revealed an overall sensitivity of 81% (71-88%) and a specificity of 90% (85-93%) in a previous study [ 4 ]. This method allows for susceptibility testing of relevant organisms, guiding antibiotic therapy.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Joint aspiration and culture are often used to confirm the diagnosis of PJI, and studies have shown that it is both sensitive and specific in patients at moderate-to-high risk. Direct aspiration revealed an overall sensitivity of 81% (71-88%) and a specificity of 90% (85-93%) in a previous study [ 4 ]. This method allows for susceptibility testing of relevant organisms, guiding antibiotic therapy.…”
Section: Discussionmentioning
confidence: 76%
“…This case presents a patient with a five-year history of Waldenström macroglobulinemia who developed PJIs in bilateral shoulders and knees following a one-year course of ibrutinib treatment. Four joints concurrently undergoing PJI is a unique finding, and few cases have been reported [ 4 ]. These previously reported cases presented clinically similar to our patient, and the diagnosis was primarily made and confirmed via joint aspiration [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations